Toxicity test of gastropoda extracts of Littorina scabra and Terebralia sulcata from Payung Island, Musi River Estuary, South Sumatra - Dimas Arie Pratama; Rozirwan Rozirwan; Muhammad Hendri (Faculty of Mathtmatics and Natural Sciences, 2021)
Gastropoda is one of the potentially most common biotas found in mangrove ecosystems and as bioactive compounds that have not been widely studied. Gastropod species Littorina scabra and Terebralia sulcata were found in the Payung Island. This research aimed to determine and compare the potential toxicity between two species of gastropod extract of L. scabra and T. sulcata. This research was conducted in February 2017. The research procedure included sampling and sample preparation, extraction, and toxicity test that Brine Shrimp Lethality Test (BSLT) method. Toxicity test showed LC50 415.58 μg/mL L. scabra while LC50 value from T. sulcata equal to 565.52 μg/mL. From the comparison, the toxicity value of L. scabra gastropod was higher than the T. sulcata type.